NGUYÊN LIỆU KHOÁNG HOẠT TÍNH TỪ MỘT SỐ ĐÁ PHUN TRÀO AXÍT VÀ TRUNG TÍNH Ở VIỆT NAM VÀ Ý NGHĨA THỰC TIỄN CỦA CHÚNG - Dương, Nguyễn Ánh (Vietnam Journal of Earth Sciences, 2012)
Natural reactivity materials from acidic and intermediate igneous rocks in Vietnam and their practical significances Puzzolan materials were formed from various types of different origins. However, in Vietnam, most previous researches were only paying attention to the basaltic formations, or artificial products such as fly ash, blast furnace slag, while the acidic or intermediate rocks are omitted. In this paper the author presents newly research results on the mineralogy, chemical composition, technical characteristics, as well as potential sources of puzzolan from some acidic igneous rocks formations (rhyolite, rhyotrachyte) in Yen Bai region, intermediate igneous rocks (andezite) and acidic igneous rocks (rhyodacite, rhyolite) formations in Lam Dong region.